Genome‐wide identification of Epstein‐Barr virus–driven promoter methylation profiles of human genes in gastric cancer cells. Issue 2 (25th July 2012) - Zhao, Junhong; Liang, Qiaoyi; Cheung, Kin‐Fai; Kang, Wei; Lung, Raymond W. M.; Tong, Joanna H. M.; To, Ka Fai; Sung, Joseph J. Y.; Yu, Jun
Abstract BACKGROUND: Aberrant methylation of tumor‐related genes has been reported in Epstein‐Barr virus (EBV)‐associated gastric cancers. This study sought to profile EBV‐driven hypermethylation in EBV‐infected cells. METHODS: The EBV‐positive AGS gastric cancer cell line (AGS‐EBV) and EBV‐negative AGS cells were used in this study. DNA methyltransferase‐3b (DNMT3b) activity was assessed by EpiQuick activity assay, and genome‐wide DNA methylation profiles were assessed by methyl‐DNA immunoprecipitation microarray assay. RESULTS: EBV infection was confirmed in AGS‐EBV cells by EBV‐encoded RNA in situ hybridization. Expression and activity of DNA methyltransferase‐3b (DNMT3b) was significantly increased in AGS‐EBV compared to AGS. Ectopic expression of LMP2A (latent membrane protein 2A) in AGS increased activity of DNMT3b. A total of 1065 genes were differentially methylated by EBV infection (fold‐changes ≥ 2, P < .05) in AGS‐EBV compared to AGS cells. The majority of the differentially methylated genes (83.2%, 886 of 1065 genes) had cytosine‐guanine dinucleotide (CpG) hypermethylation in AGS‐EBV (fold‐changes 2.43∼65.2) versus that found in AGS cells. Gene ontology analysis revealed that hypermethylated genes were enriched in the important cancer pathways (≥ 10 genes each, P ≤ .05) including mitogen‐activated protein kinase signaling, cell adhesion molecules, wnt signaling pathway, and so forth. Six novel hypermethylated candidates (IL15RA, REC8, SSTR1, EPHB6, MDGA2, and SCARF2) were further validated. Higher levels of DNA methylation were confirmed for all these genes in AGS‐EBV cells by bisulfite genomic sequencing. Furthermore, these candidates were silenced or down‐regulated in AGS‐EBV cells, but can be restored by demethylation treatment. CONCLUSIONS: EBV infection in AGS cells induced aberrant CpG hypermethylation of 886 genes involving in important cancer‐related pathways. Induction of promoter methylation by EBV is regulated by up‐regulation of DNMT3b through LMP2A. Cancer 2013. © 2012 American Cancer Society.